"Validação do estudo "Emoções no comportamento do consumidor: uma aproximação hierárquica" no setor dos vinhos". - Almeida, Daniela Ferreira Soares de (2015)
Cada vez mais os produtores sentem dificuldade em chamar a atenção do consumidor para o seu produto. Neste trabalho pretende-se validar o estudo Emotions in consumer behavior: a hierarquical approach em Portugal e ao setor dos vinhos. Com este estudo procura-se mostrar que é possível hierarquizar as emoções do consumidor em três níveis: superior (dimensões positivas e negativas),inferior (emoções específicas, definidas com base em Richins, Consumptions Emotion Set (CES)) e intermédio (emoções básicas – quatro negativas e quatro positivas). Desta forma provou-se que na estrutura hierárquica dos vinhos – licoroso e tinto –, os consumidores só identificam os afetos positivos dos negativos, enquanto as emoções do nível intermédio são agrupadas de forma diferente da proposta pelos autores. Com isto podemos concluir que as pessoas conseguem fazer uma distinção ao nível mais abstrato e geral (afeto positivo e afeto negativo); ABSTRACT: Increasingly, producers find it difficult to draw the attention of consumers for their product. This work aims to validate the study Emotions in consumer behavior: a hierarquical approach in Portugal and at the wine sector. This study seeks to show that it is possible to rank the emotions of the consumer in three levels: the top level (positive and negative dimensions), on the lower specific emotions (defined whit based on Richins, Consumptions Emotion Set (CES)) and the intermediate level (basic emotions - four positive and four negative). It is intended to reflect on the importance of emotions in buying decisions and consumption, in particularly wine. It will also check whether the results obtained by the authors for different types of food are confirmed for the wine. With this study it was proved that the hierarchical structure of the wine – liqueur and red –, the consumers only identify the positive affects of negative emotions, while the intermediate level are grouped differently than proposed by the authors. With this we can conclude that the respondents can make a distinction to the more abstract and general level (positive affect and negative affect).